Comparison of retinal vascular abnormalities in the fellow eyes of children with Coats’ disease and normal subjects using ultra-widefield fundus fluorescein angiography - Shenshen Yan; Haixia Ji; Yuzhu Liu; Haicheng She; Haiying Zhou (Photodiagnosis and Photodynamic Therapy)
Purpose: To investigate retinal vascular abnormalities in the affected and fellow eyes of children with Coats’ disease using Optos® ultra-widefield fundus fluorescein angiography (UWFFA) and compare the peripheral vascular abnormalities between fellow eyes and normal control eyes. Methods: Children diagnosed with Coats’ disease who underwent UWFFA were retrospectively reviewed. Healthy eyes with complete UWFFA data were selected as controls. Retinal vascular abnormalities of the primary affected, fellow eyes and normal control eyes were recorded by investigating the UWFFA images. Results: Among the 190 eyes of 95 patients with unilateral Coats’ disease, 83 (87.4%) were male, and the median age was 9.00 (7.00, 12.25) years (4–18 years). 93 (97.9%) fellow eyes had peripheral capillary telangiectasia that most commonly located in the temporal periphery. 59 (62.1%) fellow eyes had microaneurysms and 19 (20.0%) had vascular leakage; 29 (30.5%) fellow eyes had peripheral vascular tortuosity and 86 (90.5%) eyes had peripheral right-angle vessels. Peripheral capillary non-perfusion (CNP) were found in 31.6% (30/95) fellow eyes. We also found that the terminal vascular patterns in the fellow eyes were mainly loop pattern, accounting for 90.5%. The incidence of capillary bed abnormalities, vascular leakage, right-angle vessels and CNP were significantly higher in fellow eyes of Coats’ disease than control eyes (p<0.001, p=0.044, p<0.001, p=0.001, respectively). Regarding the terminal vascular patterns, the proportion of loop pattern in fellow eye group was significantly higher than that in control eye group (p<0.001). A total of 21 Coats’ patients had follow-up UWFFA data. The average follow-up time was 13.19±10.09 (3–35) months. There was no significant change in peripheral retinal vascular abnormalities in the fellow eye of all patients between the first and last visit. Conclusions: Because Optos® UWFFA device is able to quickly take panoramic fundus images using mild excitation light without contacting the cornea, it allows the detection of peripheral vascular changes in the fellow eyes of children with Coats’ disease. Contrary to the previous belief that Coats’ disease is a “unilateral condition”, our finding shows that Coats’ disease appears to be a highly asymmetric bilateral disease, and the peripheral vascular abnormalities in the fellow eye remains stable in short term.